2008
DOI: 10.1093/hmg/ddn066
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of X-linked adrenoleukodystrophy-associated, very long chain fatty acids on glial cells and neurons from rat hippocampus in culture

Abstract: Saturated very long chain fatty acids (VLCFAs; > or =C22:0) accumulate in X-linked adrenoleukodystrophy (X-ALD, OMIM 300100), a severe hereditary neurodegenerative disease, due to peroxisomal impairment. Previous studies analysed the development of X-ALD in humans and gene knockout animal models. However, the toxic effect of VLCFA leading to severe symptoms with progressive and multifocal demyelination, adrenal insufficiency and inflammation still remains unclear. To understand the toxic effects of VLCFA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
109
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 68 publications
7
109
0
4
Order By: Relevance
“…Neither human nor mouse AMN spinal cord displays cell death despite accumulation of LPC C26:0 42. For some time, it has been known that excess VLCFA (40 µM and above) affects membrane function and causes toxicity to adrenocortical cells, oligodendrocytes, astrocytes, and neurons 43, 44. For example, excess free VLCFA induces depolarization of mitochondria and deregulation of the intracellular calcium homeostasis,42 and in the brain, this can cause activation and apoptosis of microglia 4.…”
Section: Discussionmentioning
confidence: 99%
“…Neither human nor mouse AMN spinal cord displays cell death despite accumulation of LPC C26:0 42. For some time, it has been known that excess VLCFA (40 µM and above) affects membrane function and causes toxicity to adrenocortical cells, oligodendrocytes, astrocytes, and neurons 43, 44. For example, excess free VLCFA induces depolarization of mitochondria and deregulation of the intracellular calcium homeostasis,42 and in the brain, this can cause activation and apoptosis of microglia 4.…”
Section: Discussionmentioning
confidence: 99%
“…6A ) supports the hypothesis that LTs may contribute to the observed oxidative burden, even in the histologically normal-looking area of the cALD brain. The VLCFA C26:0 has been implicated in reductions of GSH in cultured cells ( 8 ), and it also alters calcium homeostasis and mitochondrial potential in neural cells, including oligodendrocytes ( 6 ). Redox imbalance is supported by the enhanced expression of MnSOD and HSP-70 in the normal-looking area away from the plaque ( Fig.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In the present study, we characterized the effects of C24:0 on human neuronal SK-N-BE cells. As various cytotoxic effects associated with cell death have been observed in different cell types treated with C24:0 (Kahn et al, 2011;Baarine et al, 2012;Zarrouk et al, 2012;Hein et al, 2008), we wondered whether this fatty acid is able to induce cytoskeleton modifications. Using various flow cytometric, microscopic and biochemical methods, we demonstrated changes in actin and A.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of VLCFAs have also been found in the plasma and red blood cells of patients with AD (Zarrouk, 2013). Notably, in glial and neuronal cells (Hein et al, 2008;Baarine et al, 2012;Zarrouk et al, 2012), it was previously reported that tetracosanoic acid (C24:0) (used at concentrations in the 5-20 μM range) is capable of triggering mitochondrial dysfunctions and oxidative stress associated with a non-apoptotic mode of cell death. These are regarded as important events leading to the development of AD (Kahn et al, 2011;Silva et al, 2012;von Bernhardi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation